The Saudi reaction to the Arab revolts: the paradoxical Saudi policy towards the Arab Spring - Bastaoros, Youssef Tarek (AUC Knowledge Fountain, 2015)
This thesis examines the foreign policy of the Kingdom of Saudi Arabia towards the Arab Spring that erupted in early in several Arab countries, and how Saudi Arabia dealt with these events. The reactions of Saudi Arabia towards the events of the Arab Spring seem contradictory in the sense of effectively supporting the regimes in Bahrain and Egypt whilst supporting the opposition in Libya and Syria. Several research questions are raised in this thesis, therefore this study attempts to provide answers on how a conservative status quo like the Kingdom serves its objectives in a revolutionary environment, and why Saudi Arabia applies these apparent contradictory measures in dealing with the Arab Spring. This study uses Neoclassical Realist approach to study the foreign policy behavior of Saudi Arabia towards the Arab Spring, and how Saudi Arabia dealt with the threats unleashed by the Arab Spring. Lastly, the conclusion of this thesis tests the hypotheses and offers a comprehensive understating of the Saudi reaction towards the Arab Spring from a Neoclassical Realist perspective.